Onwards and upwards - Arancha González (International Trade Forum, 2019)
The phenomenon of ‘Africa rising’ has been cited so often in the past few decades that it risks becoming a bit of a cliché. But the reality shows there is justification for this continued optimism. In July 2019 leaders of African Union nations took a decisive step toward realizing their economic aspirations with the formal launch of the African Continental Free Trade Area (AfCFTA).